Criminal Responsibility For Perpetrators Of Criminals Who Distribute Wood Produced From Illegal Logging (Analysis of the Decision of the Supreme Court of the Republic of Indonesia Number 1597 K/PID. Sus – LH/2020) - Sagala, Silvia Hermala; Yunara, Edi; Alsa, Abdul Aziz (Institute for Law and Economics Studies, 2025)
Criminal liability for perpetrators of criminal acts who distribute wood from illegal logging is an essential issue in Indonesia's forest protection context. The Analysis of the Supreme Court Decision of the Republic of Indonesia Number 1597 K/Pid.Sus-LH/2020 shows the challenges faced by law enforcement related to this illegal practice. With the increase in illegal logging threatening forest sustainability and biodiversity, this study aims to evaluate the effectiveness of criminal sanctions applied to illegal wood distributors. This study uses a normative juridical approach to review the legal framework governing these illegal acts. The study results indicate that despite strict regulations, obstacles in law enforcement, such as lack of evidence and legal awareness in the community, are significant. Therefore, strategic steps are needed to increase the effectiveness of law enforcement and encourage community participation in reporting illegal activities to maintain forest sustainability